Dietary fiber suspensions from olive mill wastewater as potential fat replacements in meatballs - Galanakis, Charis M.; Tornberg, Eva; Gekas, Vassilis (My University, 2010)
A dietary fiber containing material, named as alcohol insoluble residue (AIR), was recovered from the olive mill wastewater (OMW). It was separated into different fractions (water soluble and insoluble AIR) and characterized with regard to fiber and ion content. Dynamic rheological tests of the water soluble fraction (WSAIR) were conducted in order to examine its gelling ability. Thereafter, AIR as well as WSAIR were utilized as fat replacement in meatballs together or separately with carrot and starch and compared with regard to the total, water and fat loss or oil uptake during frying of the meatballs. Results indicated that AIR could not be considered as a potential fat replacement in meatballs due to the restricted water holding ability. Nevertheless, WSAIR could be utilized together with carrot fibers as additive in low fat meatballs, since it was able to improve the cooking properties of the product, by restricting the oil uptake and thereby giving rise to meatballs with sustained reduced fat content
Keywords: Dietary fiber; Fat replacement; Meatballs; Olive mill wastewater